Η Ίδρυση του Φιλολογικού Συλλόγου Φλώρινας «Αριστοτέλης» στη Φλώρινα την περίοδο της Κατοχής - Ηλιάδου-Τάχου, Σ. (Μακεδονικά, 2011)
The antifascist activity in the prefecture of Florina engaged different dimensions,which were related with the social origin of those that participatedin it. Thus, the representatives of the rural and working layers included themselves in the EAM party, while urban population, when they were found inthe maelstrom of international conspiracies at the expense Makedonia, selected the approach with the Germans in order to face the Bulgarian drawingsfor the region. The most crucial arm of cultural sovereignty used by the Greekbourgeois of Florina was the projection of «Hellenism» of the region and ofthe residents. The Association «Aristotelis» was called to serve this goal, thatis to appear the Greek cultural heritage against the Bulgarian infiltration. Theeffort of urban class was focused on developing relations with the German side in order to face Bulgarians. This effort however was proved particularlyfragile after Thomaidis, the Director of the «Aristotlis’» Chorus, had beenmurdered in Kladorahi in 1943. As after this murder, the effectiveness ofstrategy, which was being followed by «Aristotelis», began to enter in contestation.